The nuclear receptors SF1 and COUP-TFII cooperate on the Insl3 promoter in Leydig cells. Issue 2 (27th June 2022) - Di-Luoffo, Mickaël; Pierre, Kenley Joule; Robert, Nicholas M; Girard, Marie-Joëlle; Tremblay, Jacques J
Abstract : In brief: The insulin-like 3 (INSL3) hormone produced by Leydig cells is essential for proper male sex differentiation, but the regulation of Insl3 expression remains poorly understood. This study describes a new physical and functional cooperation between the nuclear receptors SF1 and COUP-TFII in Insl3 expression. Abstract: INSL3, a hormone abundantly produced by Leydig cells, is essential for testis descent during fetal life and bone metabolism in adults. The mechanisms regulating Insl3 expression in Leydig cells have been studied in several species but remain poorly understood. To date, only a handful of transcription factors are known to activate the Insl3 promoter and include the nuclear receptors AR, NUR77, COUP-TFII, and SF1, as well as the Krüppel-like factor KLF6. Some of these transcription factors are known to transcriptionally cooperate on the Insl3 promoter, but the mechanisms at play remain unknown. Here, we report that COUP-TFII and SF1 functionally cooperate on the Insl3 promoter from various species but not on the Inha, Akr1c14, Cyp17a1, Hsd3b1, Star, Gsta3, and Amhr2 promoters that are known to be regulated by COUP-TFII and/or SF1. The Insl3 promoter contains species-conserved binding sites for COUP-TFII (−91 bp) and SF1 (−134 bp). Mutation of either the COUP-TFII or the SF1 sequence had no impact on the COUP-TFII/SF1 cooperation, but the mutation of both binding sites abolished the cooperation. In agreement with this, we found that COUP-TFII and SF1 physically interact in Leydig cells. Finally, we report that the transcriptional cooperation is not limited to COUP-TFII and SF1 as it also occurred between all NR2F and NR5A family members. Our data provide new mechanistic insights into the cooperation between the orphan nuclear receptors COUP-TFII and SF1 in the regulation of Insl3 gene expression in Leydig cells.